The relevance of sufistic reasoning to religious modernization: values of religious harmonization in wahdatal-adyan sufism - Selamat, Kasmuri (Linguistics and Culture Review, 2021)
Conflicts vis-a-vis religious pluralism most often emerge in the face of Indonesian Islam. Religion is polarized into a practical-political dimension. Religious issues are raised for the interests of individuals or power-driven groups. The notion concerning the defense of God becomes a utopian notion. Faith is then oriented towards religion as an institution but not towards God. Hence, the followers of other religions or groups having different beliefs are not regarded as God’s worshipers. Coping with the aforesaid case, the government is continuously echoing the strategy of religious moderation. However, to a few points, such an effort is not yet effective. Furthermore, how is the relevance of Wahdat al-Adyan Sufistic reasoning as a foundation of religious moderation? This study used a critical analysis approach to the concept of wahdatul adyan proposed by Ibn ‘Arabi. The researcher sought to contextualize it with the historical development of Islam in Indonesia. The findings demonstrated an important point that Sufistic reasoning as the foundation of religious moderation historically has relevance to Indonesian Islam.